Consistent Riccati expansion solvability and soliton–cnoidal wave solutions of a coupled KdV system. (January 2023) - Wu, Huiling; Song, Junfeng; Zhu, Quanyong
Abstract: The consistent Riccati expansion (CRE) solvability of a coupled KdV system is investigated with the aid of the Riccati equation. Differing from the complete Painlevé integrability for three branches, this coupled KdV system is shown to be CRE solvable for one branch and non-CRE solvable for two other branches. Based on the last consistent differential equation under the CRE solvable case, a kind of soliton–cnoidal wave interaction solution is derived explicitly.